Kajian Morfologi Bahasa Melayu Riau di Desa Serapung - Sarini Zarem; Alber (UIR Press, 2022)
Composition as a tool to study a language. Language has its own differences depending on the speaker interprets it. Riau Malay language has differences due to differences in Riau Malay language caused by geographical location. Different geographical locations lead to the emergence of different words that affect changes in form and meaning. Forms and meanings in a language have different meanings, depending on how speakers interpret them. The purpose of this study is to describe, analyze, identify, and conclude the form and meaning of the composition of the Riau Malay language in Serapung village, Kuala Kampar sub-district, Pelalawan district: a morphological study. The theory used in this research is the theory of Muslich and Muchti. This research uses ethnographic method. Sources of data used are oral data or oral speech. The results of this study can be concluded as a whole found (1) compositional forms in which the first element is explained (D) by the second element (M), (2) compound forms whose elements do not explain each other, but are only a parallel series (copulative), (3) the meaning of composition which states the meaning of dregs/dung, (4) the meaning of composition which states the meaning of biological family (5) the meaning of composition which states the meaning of circumstances, (6) the meaning of composition which states the meaning of nature and (7) the meaning of composition which states the meaning tool.